Allah's best friend: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story highlights the bond between Allah and His devoted servant, showcasing how unwavering faith and love can strengthen one's connection to the divine. It emphasizes the importance of trust and loyalty in a believer's life.